Towards European Science 2015
DOI: 10.4337/9781782545514.00015
|View full text |Cite
|
Sign up to set email alerts
|

The internationalisation of research institutes

Abstract: Governments continue to be key players in research, despite the significance of private investments. Governments' direct funding, regulations and incentives are essential factors and mechanisms in steering and funding research (OECD 2011b). However countries differ in the basic features and the institutional arrangements of their

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The emphasis was no longer on collaboration per se, but more on global competition and research excellence (Luukkonen & Nedeva, 2010). Stronger focus on competition actually fosters research collaboration since staying at the frontier of worldwide science requires joint effort and resources (Cruz-Castro, Jonkers, & Sanz-Menéndez, 2015). This shift was compliant with increased interest at EU political forums in research and knowledge production, as manifested in the Lisbon Strategy.…”
Section: Integrating Europementioning
confidence: 99%
“…The emphasis was no longer on collaboration per se, but more on global competition and research excellence (Luukkonen & Nedeva, 2010). Stronger focus on competition actually fosters research collaboration since staying at the frontier of worldwide science requires joint effort and resources (Cruz-Castro, Jonkers, & Sanz-Menéndez, 2015). This shift was compliant with increased interest at EU political forums in research and knowledge production, as manifested in the Lisbon Strategy.…”
Section: Integrating Europementioning
confidence: 99%
“…More analytically grounded, the research of Cruz-Castro et al ( 2015 ) or Sanz-Menéndez et al ( 2011 ) identified two attributes of research organisations likely to condition research agendas: (a) the degree of external autonomy and resource dependence of the organisation—in terms of funding, human resources, access to external knowledge, for instance—and the associated degree of autonomy and discretion over resources; (b) the type of internal authority structure characterising the functioning of the organisation, and more precisely the relationship between centres’ researchers and management. Based on these dimensions, they constructed a typology of research organisations in correspondence with some empirical cases.…”
Section: Research Funding and Authority Sharingmentioning
confidence: 99%
“…With respect to our objective to understand what drives PROs to vertically integrate or outsource knowledge transfer management activities, this literature suffers from two main limitations. First, findings from studies of universities cannot be immediately transposed to PROs, which are different in many respects, including: (i) their activities (PROs' teaching activities, when they exist at all, are limited to doctoral supervision and professional training, and PROs' research activities are often closely directed to the achievement of government objectives (Cruz-Castro et al, 2015); (ii) their subject focus (PROs tend to specialise in one field or a few closely related fields, while universities can have very diversified subject portfolios); (iii) their governance (PROs can have varied ownership and management structures, and can be affiliated with different parts of government (Sanz-Menéndez et al, 2011), whereas universities usually maintain an arms' length relationship with government whose role is limited to funding provision). Secondly, studies in this stream of research tend to be descriptive, paying limited attention to the conceptualisation of the choice of organisational approach in more theoretical terms.…”
Section: Knowledge Transfer Management In Prosmentioning
confidence: 99%